2018
DOI: 10.1021/acs.jafc.7b06118
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Analytical Method for Analyzing Pyrrolizidine Alkaloids in Different Groups of Food by UPLC-MS/MS

Abstract: Suspected nontargeted pyrrolizidine alkaloids (PAs), without analytical reference standard, were observed and interfered with the determination of targeted PAs in complex food matrices, especially for spices samples. Selectivity and applicability of multiple reaction monitoring (MRM) transitions, multistage fragmentation (MS3), and MRM with differential ion mobility spectrometry (DMS) for eliminating false positive identifications were evaluated. Afterward, a selective and sensitive LC-MS/MS method for the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…On the contrary, the use of HRMS technologies, and in particular those using hybrid approaches like Q-Orbitrap or Q-TOF, enables ultra-high resolving power values, and are very promising in the analysis of this class of natural toxins [ 89 ]. Moreover, multistage fragmentation (MS n ) or differential ion mobility mass spectrometry can be considered very helpful in discriminating isobaric compounds [ 90 ]. In June 2015, the European Commission issued the Recommendation (EU) 2015/976 on the monitoring of the presence of TAs in food and on the method of analysis that should preferably be HPLC-MS/MS or, if not possible, GC-MS.…”
Section: Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the use of HRMS technologies, and in particular those using hybrid approaches like Q-Orbitrap or Q-TOF, enables ultra-high resolving power values, and are very promising in the analysis of this class of natural toxins [ 89 ]. Moreover, multistage fragmentation (MS n ) or differential ion mobility mass spectrometry can be considered very helpful in discriminating isobaric compounds [ 90 ]. In June 2015, the European Commission issued the Recommendation (EU) 2015/976 on the monitoring of the presence of TAs in food and on the method of analysis that should preferably be HPLC-MS/MS or, if not possible, GC-MS.…”
Section: Alkaloidsmentioning
confidence: 99%
“…In another study, a UPLC-MS/MS analytical method was proposed for the determination of 15 PAs and 13 respective N-oxides in different groups of food [ 90 ]. The ultrasonic assisted SLE and the clean-up through the C18 SPE column allowed the application of the method to several matrices including cow milk, tea infusion, honey, cooked chicken, egg, cooked beef, barley flour and clove leaves.…”
Section: Alkaloidsmentioning
confidence: 99%
“…It was reported that PAs showed a degradation possibility under a high concentration of ammonium hydroxide. 34 Therefore, 3 vol% ammonium hydroxide in methanol was selected as the final optimized elution solvent. Figure 3 shows the total ion chromatograms of PAs extracted from an Emilia sonchifolia sample before and after being treated by SPE.…”
Section: Solid Phase Extractionmentioning
confidence: 99%
“…Considering the intoxication of PAs, many researchers have reported the detection of PAs in foodstuffs and herbal plants by using spectrophotometry , HPLC , MEKC , LC‐MS , GC‐MS , etc. Owing to the complexity of matrices, the majority of these reports resorted to at least one or more clean‐up steps to separate and enrich enough amounts of PAs for the analysis.…”
Section: Introductionmentioning
confidence: 99%